2021
DOI: 10.1093/cid/ciab944
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Testing and Diagnosis Among People With Human Immunodeficiency Virus (HIV) Engaged in Care at 4 US Clinical Sites, 2014-2018

Abstract: Background Despite rising rates of syphilis among people with HIV (PWH) in the United States, there is no optimal syphilis screening frequency or prioritization. Methods We reviewed records of all PWH in care between January 1, 2014 and November 16, 2018 from four sites in the CFAR Network of Integrated Clinical Systems Cohort (CNICS; N=8455). We calculated rates of syphilis testing and incident syphilis and used Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
12
2
Order By: Relevance
“…Incidence rate was 3.77 cases per 100 person-years for infection, and 6.47 cases per 100 person-years for re-infection, confirming that syphilis occurs more frequently in previously infected subjects, and reflecting the lack of prevention measures. As a comparison, a recent study found a comparable incidence rate of syphilis of 4,7 per 100 person-years in a cohort of PLWH from the United States [ 21 ]. However, unlike ours, this study found higher rates among younger MSM and those with detectable HIV viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rate was 3.77 cases per 100 person-years for infection, and 6.47 cases per 100 person-years for re-infection, confirming that syphilis occurs more frequently in previously infected subjects, and reflecting the lack of prevention measures. As a comparison, a recent study found a comparable incidence rate of syphilis of 4,7 per 100 person-years in a cohort of PLWH from the United States [ 21 ]. However, unlike ours, this study found higher rates among younger MSM and those with detectable HIV viral load.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that PWH who practice condomless insertive sex may be more likely to transmit HIV in the setting of both STI-related genital inflammation and detectable plasma HIV RNA compared with those with a suppressed viral load. We also found that an incident syphilis diagnosis in PWH was strongly associated with detectable HIV RNA, raising concerns that urogenital GC/CT and syphilis could potentiate onward HIV transmission [ 11 ]. While mathematical modeling studies have assessed the contribution of GC/CT to HIV transmission [ 10 ], future modeling studies of HIV transmission should incorporate the effects of both site-specific GC/CT and syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported on the criteria used to assess syphilis diagnoses in a clinical cohort [ 11 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Recent studies found syphilis to be common among women with HIV, particularly young women, Black and Hispanic women of all ages, women who inject drugs, and women with hepatitis C virus. 4,5 Syphilis screening using the traditional or reverse algorithm is an important intervention to address the rising rates of syphilis among PLWH. Although the reverse algorithm may diagnose syphilis earlier than the traditional algorithm, 6 it cannot be used to detect a new Treponema pallidum infection among those with a history of syphilis and is inefficient and not cost-effective in populations with a high prevalence of prior syphilis.…”
mentioning
confidence: 99%